2021
DOI: 10.3390/ijms221910354
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comprehensive Analysis of the Nuclear Factor-Y Family Genes Reveal Their Multiple Roles in Response to Nutrient Deficiencies in Brassica napus

Abstract: Nuclear Factor-Y (NF-Y) transcription factors play vital roles in plant abiotic stress response. Here, the NF-Y family in Brassica napus, which is hyper-sensitive to nitrogen (N) deprivation, was comprehensively identified and systematically characterized. A total of 108 NF-Y family members were identified in B. napus and categorized into three subfamilies (38 NF-YA, 46 NF-YB and 24 NF-YC; part of the Arabidopsis NF-YC homologous genes had been lost during B. napus evolution). In addition, the expansion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…To better understand the biological functions of the PcNF-YAs, an exon-intron structure analysis of the PcNF-YA genes was performed and showed that the number of exons in most PcNF-YA genes was five. This finding was consistent with the results for Brassica napus [ 35 ], S. tuberosum [ 15 ], R. communis [ 14 ] and Prunus persica [ 11 ]. This evidence indicates that the structure of PcNF-YA genes is relatively stable and evolutionarily conserved.…”
Section: Discussionsupporting
confidence: 92%
“…To better understand the biological functions of the PcNF-YAs, an exon-intron structure analysis of the PcNF-YA genes was performed and showed that the number of exons in most PcNF-YA genes was five. This finding was consistent with the results for Brassica napus [ 35 ], S. tuberosum [ 15 ], R. communis [ 14 ] and Prunus persica [ 11 ]. This evidence indicates that the structure of PcNF-YA genes is relatively stable and evolutionarily conserved.…”
Section: Discussionsupporting
confidence: 92%
“…After nine days of growth, the plants were transferred to nutrient solution free of N, P or K for seven days. The same amount of NaCl were applied instead of NaNO 3 , NaH 2 PO 4 •2H 2 O and KCl in the three nutrient deficiency treatments, respectively [70]. For the ammonium toxicity treatment, plants were treated with nutrient solution containing 6 mM NH 4 Cl instead of NaNO 3 for 9 days.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…In general, homologous genes in the same species show differences in their expression in response to abiotic stress and hormonal treatment, suggesting that they may play different roles in stress resistance [ 27 , 28 , 29 ]. In this study, the MsRCI2D,-E genes in alfalfa could respond to salt and alkali stress and be regulated by ABA; the expression levels of the MsRCI2D,-E genes in roots and leaves showed an overall trend first increasing and then decreasing, but the up-regulation of the MsRCI2E gene was more rapid than that of the MsRCI2D gene ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%